Problem-Based Learning Assisted by Teaching Modules on the Classification of Living Things - Dari, Suci Wulan; Safitri, Novi Amelia; Chanafi, Muhammad Irfandzi; Murtafiah, Himatul; Husna, Minhatul; Azzahra, Aulia Faradina Dwi Nabila (Bioeducation Journal, 2025)
A good modul ajar is the main foundation for creating meaningful learning for students. This study aims to produce a suitable teaching module on the subject of Classification of Living Things. The type of research used is Research and Development (R&D) with a 4-D model that includes the stages of Define, Design, Develop, and Disseminate. The research subjects consisted of 18 students from class X-H, selected using random sampling techniques, and teachers involved in the validation process. The research data consisted of students' cognitive scores and module validation instruments, which were collected through learning outcome tests in the form of student concept comprehension sheets. The data were analyzed quantitatively using SPSS XXVII software to measure the effectiveness of the teaching module. The results showed that the modul ajar developed had gone through all stages of development and revision based on validator input. In addition, it also showed an average student score of 89.1 it can be concluded that this modul ajar is suitable for implementation in grade X and is effective in helping students understand the concept of the Classification of Living Things. Thus, the modul ajar is expected to have a positive impact in supporting a significant improvement in students' conceptual understanding.